A Cognitive Model of Chinese Word Segmentation for Machine Translation - Wu, Zhijie (Meta, 2011)
The Chinese language, unlike English, is written without marked word boundaries, and Chinese word segmentation is often referred to as the bottleneck for Chinese-English machine translation. The current word-segmentation systems in machine translation are either linguistically-oriented or statistically-oriented. Chinese, however, is a pragmatically-oriented language, which explains why the existing Chinese word segmentation systems in machine translation are not successful in dealing with the language. Based on a language investigation consisting of two surveys and eight interviews, and its findings concerning how Chinese people segment a Chinese sentence into words in their reading, we have developed a new word-segmentation model, aiming to address the word-segmentation problem in machine translation from a cognitive perspective.